Evaluation Study on Functioning of Community Health Centres - Planning Commission (Planning Commission, 1999)
The Community Health Centre (CHC), the third tier of the network of rural health care institutions, was required to act primarily as a referral centre (for the neighbouring PHCs, usually 4 in number) for the patients requiring specialised health care services. The objective of having a referral centre for the primary health care institutions was two-fold; to make modem health care services accessible to the rural people and to ease the overcrowding in the district hospitals. The CHCs were accordingly designed to be equipped with : four specialists in the areas of medicine, surgery, paediatrics and gynaecology; 30 beds for indoor patients; operation theatre, labour room, X-ray machine, pathological laboratory, standby generator, etc., along with the complementary medical and para medical staff.
Programme Evaluation Organisation Planning Commission Government of India New Delhi